The Effect of Mingle Model to Improve Reading Skills for Students with Dyslexia in Primary School - Irdamurni Irdamurni; Kasiyati Kasiyati; Zulmiyetri Zulmiyetri; Johandri Taufan (Journal of ICSAR, 2018)
Dyslexia is a cognitive process failure in acquiring information when reading. Children normally have been able to read at the age of 6 or 7 while children with dyslexia might still struggle with reading even when they reach 12. This research was conducted by mingle model in order to improve reading skills for dyslexic students in primary grades. The subjects selected were 23 students with dyslexia in primary grades. The research used purposive sampling and the data collected by conducting the reading test to the students. Descriptive analysis was performed as the method and intervention technique employed was mingle model. The research was carried out continually in seven days. The assessment presented in pre-intervention and post-intervention (47% and 71% respectively) showed improvement in the average value in reading skills. Findings showed that mingle model had significantly improved dyslexic students’ reading skills in primary grades.